Comparison of new-generation drug-eluting stents versus drug-coated balloon for in-stent restenosis: a meta-analysis of randomised controlled trials. Issue 2 (22nd February 2018) - Cai, Jin-Zan; Zhu, Yong-Xiang; Wang, Xin-Yu; Bourantas, Christos V; Iqbal, Javaid; Zhu, Hao; Cummins, Paul; Dong, Sheng-jie; Mathur, Anthony; Zhang, Yao-Jun
Abstract : Objective: The study sought to compare angiographic and clinical outcomes of new-generation drug-eluting stents (DES) versus drug-coated balloon (DCB) in patients with coronary in-stent restenosis (ISR). Design: Meta-analysis using data from randomised trial found by searches on PubMed, the Cochrane Library, ClinicalTrials.gov and websites of major cardiovascular congresses. Setting: Only randomised trials comparing DES with DCB were included. Participants: Patients with ISR in the included trials. Interventions: New-generation DES versus DCB. Outcomes: The angiographic and clinical outcomes including cardiac death, all-cause death, myocardial infarction, target lesion revascularisation (TLR), target vessel revascularisation (TVR), major adverse cardiac events (MACE) and stent thrombosis were investigated. Results: Five trials including 913 patients were eligible and included. Pooled analysis in angiographic results identified that new-generation DES were associated with higher acute luminal gain (−0.31 mm, 95% CI −0.42 to −0.20, P<0.001) and lower per cent diameter stenosis (risk ratio (RR): 0.28, 95% CI 0.02 to 0.55, P=0.04). DES significantly reduced the risk of TLR (RR: 1.96, 95% CI 1.17 to 3.28, P=0.01) compared with DCB; however, there was no statistical differences for MACE (RR: 1.21, 95% CI 0.67 to 2.17, P=0.53), myocardial infarction (RR: 1.16, 95% CI 0.55 to 2.48, P=0.69) and cardiac death (RR: 1.80, 95% CI 0.60 to 5.39, P=0.29). Conclusions: Interventions with new-generation DES appear to be associated with significant reduction in per cent diameter stenosis and TLR at short-term follow-up, but had similar MACE, myocardial infarction and cardiac death for patients with coronary ISR compared with DCB. Appropriately powered studies with longer term follow-up are warranted to confirm these findings.